2012
DOI: 10.1167/iovs.11-9153
|View full text |Cite
|
Sign up to set email alerts
|

Visual Function and Vision-Related Quality of Life after Vitrectomy for Epiretinal Membranes: A 12-Month Follow-up Study

Abstract: Removing ERMs improved visual function, anatomy, and the VR-QOL. Three months postoperatively, the improved BCVA was the most important factor related to the improved VR-QOL, although the simultaneous cataract surgery might have had a confounding effect. The improved metamorphopsia was the important factor associated with improved VR-QOL 12 months postoperatively.(www.umin.ac.jp/ctr number, UMIN000000617).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
1
16
1
1
Order By: Relevance
“…This study has some limitations: the small sample size analyzed might have influenced the power of the study, the incomplete follow-up of some patients (only 67% at four years), and the absence of a quantification of metamorphopsia (e.g., M-Chart) providing another quality of life parameter [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study has some limitations: the small sample size analyzed might have influenced the power of the study, the incomplete follow-up of some patients (only 67% at four years), and the absence of a quantification of metamorphopsia (e.g., M-Chart) providing another quality of life parameter [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ghazi-Nouri et al (2006) found PRO to correlate with binocular BCVA at a follow-up of 4 months. Another study by Matsuoka et al (2012) had a follow-up after 3 and 12 months and found a correlation between binocular BCVA and PRO at 3 months but no correlation at 12 months. As BCVA has been shown to improve up to 1 year or longer after ERM surgery (Thompson 2005;Kinoshita et al 2016), the difference in follow-up (3 months versus 1-3 years) might explain the discrepancy between the results.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we describe a new method for measuring perceptual changes in patients that overcomes many of the limitations of existing subjective techniques, and evaluated it using the iERM disease model. Accurate measurement of metamorphopsia can provide crucial information to guide clinicians in the management of vitreomacular interface diseases 27 . Although conditions such as exudative age-related macular degeneration use techniques such as the Amsler grid for screening for the development of acute onset functional changes 28 , there is a potential clinical benefit for the quantification of visual functions in chronic or slowly progressive diseases such as iERMs.…”
Section: Discussionmentioning
confidence: 99%